Extraction of a single Stokes line from a Brillouin fibre laser using a silicon oxynitride microring filter - Zulkifli, M.Z.; Chong, W.Y.; Melloni, A.; Morichetti, F.; Harun, Sulaiman Wadi; Ahmad, Harith (IOP Publishing, 2013)
Extraction of a single channel Brillouin Stokes line generated by pumping a length of single mode fibre is demonstrated using a silicon oxynitride microring resonator. The high Q-factor microring resonator has a steep slope transmission profile with an extinction ratio of 20 dB and a free spectral range of 0.4 nm. Experimental results show that extraction of a single Brillouin Stokes line can be achieved with a side mode suppression ratio of more than 12 dB. Additionally, Brillouin Stokes line selection can be achieved by controlling the microring resonance wavelength by thermal tuning.